Analysis of Jungle Zone Tourism Communication at Tahura, Berastagi - Nurbani, Nurbani; Ananda, Sabilla Tri (Komunikologi: Jurnal Pengembangan Ilmu Komunikasi dan Sosial, 2025)
This research aim to analyze the tourism communication strategy implement in managing Jungle Zone in Tahura, Berastagi in the perception of management and visitors of Jungle Zone Additionally, this research analyze how Jungle Zone managemers understand sustainable tourism to minimize negative environmental impacts. Using a qualitative method with data collection techniques including interviews, observations, and literature reviews, the researcher interviewed 5 key informants, one manager and four visitors. Based on the data analysis results, it can be concluded that the management of Jungle Zone implements a Word of Mouth Communication marketing strategy by providing free admission to visitors who are students and local residents, hoping that these visitors will promote Jungle Zone to their relatives. Tourism promotion strategies are also implemented by actively uploading visitor activities to the Jungle Zone Instagram account. In terms of environmental sustainability, the management understands the importance of caring for the Tahura environment as much as possible to minimize its negative impact on the environment.